Perlindungan Konsumen Atas Pelanggaran Hak Dalam Perjanjian Jual Beli Tiket Konser Dan Fasilitas Terkait Oleh Promotor - Aprilla Laura Utari; Alya Syiendi Fadillah1 (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Consumer behavior analysis is a method used to understand how people, groups, or institutions select, use, and stop using goods and services, and how their experiences influence their shopping decisions. In this situation, numerous elements that influence buyer behavior, such as choices, needs, drives, and views on certain products or services. (Supriyono, 2024) reviewed customer protection in the context of the cancellation of music concerts and online ticket sales in Indonesia. It is explained that this protection is regulated in Law Number 8 of 1999 and the Civil Code, which requires business actors to be responsible for the products and services provided and to provide compensation if violations occur. Cases of unilateral cancellations by organizers and fraudulent practices by third parties selling fake tickets make it difficult for consumers to obtain their rights, such as refunds. The rapidly growing music industry and high public interest in concerts pose their own challenges in consumer protection and the regulation of promoter businesses. Therefore, it is essential to Reinforce the legal structure and supervision so that consumer rights are optimally protected